One-gateway system in managing campus information system using microservices architecture - Salim, Yulita; Muis, Ismunandar; Syafie, Lukman; Azis , Huzain; Rachman Manga, Abdul (Association for Scientific Computing Electrical and Engineering, 2023)
Universitas Muslim Indonesia (UMI) has developed several applications for managing the campus's digital information and management systems, both internally and externally. However, several applications were previously created in the development of information system applications at UMI. However, these applications were not well-suited for long-term use due to their complexity and lack of integration. Therefore, UMI aims to create a fully integrated and well-managed campus information system by implementing the concept of microservices. The microservices approach involves dividing large applications into smaller interconnected components. This approach facilitates the management of application systems and enables better integration. Moreover, the microservices approach simplifies system maintenance for application developers, as each application is separated into smaller components